Tax Elasticity Estimates for Capital Stocks in Canada - Wen, Jean-Francois (IMF Working Papers; Working Paper ;, 2020)
The paper provides estimates of the long-run, tax-adjusted, user cost elasticity of capital (UCE) in a small open economy, exploiting three sources of variation in Canadian tax policy: across provinces, industries, and years. Estimates of the UCE with Canadian data are less prone to the endogeneity problems arising from the effects of tax policy changes on the interest rate or on the price of capital equipment. Reductions in the federal corporate income tax rate during the early 2000s for service industries but not for manufacturing, which already benefited from a preferential tax rate, contribute to the identification of the UCE. To capture the long-run relationship between the capital stock and the user cost of capital, an error correction model (ECM) is estimated. Supplementary results are obtained from a distributed lag model in first differences (DLM). With the ECM, our baseline UCE for machinery and equipment (M and E) is -1.312. The corresponding semi-elasticity of the stock of M and E with respect to the METR is about -0.2, suggesting, for example, that a 5 percentage point reduction in the METR, say from 15 to 10 percent, would in the long run generate an increase of 1.0 percent in the stock of M and E. The UCE for non-residential construction is statistically insignificantly different from zero.